COHESIVE DEVICES (CDS) IN EXPOSITORY ESSAY WRITTEN BY INDONESIAN STUDENTS OF ENGLISH AS A FOREIGN LANGUAGE (EFL) - Leti Marsetia Nilopa; M Zaini Miftah; Aris Sugianto (Premise: Journal of English Education and Applied Linguistics, 2017)
The study aims at describing the types of cohesive devices used by the third semester students of English Department of Tarbiyah Faculty of State Institute for Islamic Studies (IAIN) of Palangka Raya who took Essay Writing Course. The subjects of the study were thirteen (13) of the third semester students’ of English department of Tarbiyah Faculty of State Institute for Islamic Studies (IAIN) of Palangka Rayawho took Essay Writing Course. In order to get the data, the students were asked to write expository essays by choosing the following topics which include; (1) why the teachers should be profesional, (2) the use of digitial technology in learning and (3) how to prevent forest from a fire. The data were analysed based on Halliday and Hasan’s (1976) framework on cohesive devices covering  reference, substitution, ellipsis, conjunction and lexical cohesion. The study shows that (1) the types of cohesive devices to be found in in the students’ essays are conjunction (43.25%), reference (33.73%) and lexical cohesion (23.01%). Although there are a few cohesive devices to be used, the majority of the students’opinion essaya fail to achieve cohesion.